Recent Advances in Porous Carbon Materials for Electrochemical Energy Storage - Wang, Libin; Hu, Xianluo (Chemistry, an Asian journal, 2018)
Climate change and the energy crisis have promoted the rapid development of electrochemical energy‐storage devices. Owing to many intriguing physicochemical properties, such as excellent chemical stability, high electronic conductivity, and a large specific surface area, porous carbon materials have always been considering as a promising candidate for electrochemical energy storage. To date, a wide variety of porous carbon materials based upon molecular design, pore control, and compositional tailoring have been proposed for energy‐storage applications. This focus review summarizes recent advances in the synthesis of various porous carbon materials from the view of energy storage, particularly in the past three years. Their applications in representative electrochemical energy‐storage devices, such as lithium‐ion batteries, supercapacitors, and lithium‐ion hybrid capacitors, are discussed in this review, with a look forward to offer some inspiration and guidelines for the exploitation of advanced carbon‐based energy‐storage materials. C, how versatile! Various porous carbon materials have been widely used as electrode materials in energy storage and transfer devices (see figure). Recent advances in the synthesis of porous carbon materials from the view of energy storage, particularly in the past three years, are summarized. Representative applications in lithium‐ion batteries, supercapacitors, and lithium‐ion hybrid capacitors are discussed.